The Structural Elaboration of Board Independence: Executive Power, Institutional Logics, and the Adoption of CEO-Only Board Structures in U.S. Corporate Governance - Joseph, John; Ocasio, William; McDonnell, Mary-Hunter (Academy of Management Journal, 2014)
This study builds on structural elaboration theory by developing a model to explain the adoption of board structures that appear to conform to the prevailing institutional logic, but which in fact contradict it. We test our theory with the case of CEO-only board structures, a formal increase in board independence that prior research has shown to lead to greater CEO entrenchment rather than increased shareholder value. Using an event history analysis of the Fortune 250 over a 27-year period, we examine three mechanisms that drive its adoption: executive interests, executive power, and elaboration opportunities. We show that the CEO-only structure is more likely to occur in firms in which a higher proportion of insiders predate the CEO, and in which the CEO has greater formal power and agenda control. We also find that powerful CEOs are more likely to realize the structural change following institutional opportunities, such as the passage of Sarbanes-Oxley (SOX), and organizational contingencies, such as positive changes in firm performance. By exploring the mechanisms leading to the proliferation of the CEO-only structure, our study contributes to sociopolitical perspectives on corporate governance, as well as to theories of institutional logics and structural elaboration.